Analisis Pengaruh Literasi Keuangan, Perilaku Keuangan Dan Pendapatan Terhadap Keputusan Investasi Reksadana - Tia Aryani; Fathihani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Technological developments can be a benchmark for investors in making investment decisions. The purpose of this study was to determine the effect of financial literacy, financial behavior, and income on investment decisions for the Millennial Generation in DKI Jakarta. The data used is primary data in the form of a questionnaire distributed to 100 respondents selected using the Slovin formula. This study uses the Theory of Planned Behavior (TPB). The results of this study indicate that financial literacy has a positive and significant effect on investment decisions. Financial behavior has no effect on investment decisions. Income has no effect on investment decisions. Financial literacy, financial behavior, and income simultaneously have a significant effect on investment decisions (a case study of the Millennial Generation in DKI Jakarta)